If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -8) = -30(x + -2) Reorder the terms: 6(-8 + x) = -30(x + -2) (-8 * 6 + x * 6) = -30(x + -2) (-48 + 6x) = -30(x + -2) Reorder the terms: -48 + 6x = -30(-2 + x) -48 + 6x = (-2 * -30 + x * -30) -48 + 6x = (60 + -30x) Solving -48 + 6x = 60 + -30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30x' to each side of the equation. -48 + 6x + 30x = 60 + -30x + 30x Combine like terms: 6x + 30x = 36x -48 + 36x = 60 + -30x + 30x Combine like terms: -30x + 30x = 0 -48 + 36x = 60 + 0 -48 + 36x = 60 Add '48' to each side of the equation. -48 + 48 + 36x = 60 + 48 Combine like terms: -48 + 48 = 0 0 + 36x = 60 + 48 36x = 60 + 48 Combine like terms: 60 + 48 = 108 36x = 108 Divide each side by '36'. x = 3 Simplifying x = 3
| 2x^2+14=6x | | p(p+3)=-2 | | -y=2x-4 | | 6(x-2)=-30(x-8) | | 8r-7=25 | | 3.1x-7=2.8x+8 | | 15x+2+6x-11=180 | | 3(x-2)-(x+2)=2(x-2)+24 | | 4(3x+11)=5(x+6) | | 2.5*10-12= | | L[c(t)]=L[5t] | | .4166666667=-.5z | | d(z)=z^2-z+7 | | 0.3y=7.53 | | -3+4x=2x+7 | | -8(x-3)=-7(x-2) | | 6(x-2)=-2(6-3x) | | 6-5=+10 | | 5x-6=9+5x | | 3-x=-23 | | 6x=o | | 7/8(x-8)=24 | | 12+4+x-7+8+8x= | | 12+4(2-3)=3z+1 | | 3x-2(3x+5)=8 | | 3.5x=-44.45 | | 3/5(5x-15)=-12 | | 3(4x-5)+5(5x-6)=-297 | | 16y=3(5y-2) | | 9+5y=24 | | 47=-4f-2f-7 | | -5p+-3p-10p=18 |